PENGARUH SELF EFFICACY TERHADAP PROKRASTINASI AKADEMIK PADA SISWA SEKOLAH MENENGAH KEJURUAN NEGERI 1 LIKUPANG BARAT - Anjarrahma D. Hanjani; Jofie H. Mandang; Sinta E. J. Kaunang (Program Studi Psikologi Universitas Negeri Manado, 2022)
Academic procrastination is an interesting object of study because it influences many other important variables. Much literature evidence states that self-efficacy is a significant predictor of academic procrastination. This study aims to determine the effect of self-efficacy on academic procrastination in students. This research is a causal correlation type with a quantitative approach. Data on self-efficacy and academic procrastination scales were filled in by 51 subjects out of a total population of 108 students obtained randomly through simple random sampling using the Taro Yamane formula. The descriptive analysis stated that students' self-efficacy was in the high category and academic procrastination was in the low category. The results of the assumption test state that the research data is normal and linear in shape. The results of the simple regression analysis stated that there was a negative and significant effect of the self-efficacy variable on academic procrastination (p=0.000; p<0.05 with a contribution of 58.6%. This means that the higher the self-efficacy, the academic procrastination will decrease and vice versa. It is recommended that research The next section discusses active academic procrastination.